Discussion on the Classification of Chinese Flour Products - WEI Yi-min (Liang you shipin ke-ji)
Taxonomy aims to elucidate the historical origin and interrelationship among species (plant-based products), so that the established taxonomy system reflects the kinship and evolutionary history of species (plant products). The significance of food taxonomy is to reveal the origin and evolution of food, as well as the relationship between food diversity and culture, and involves industrial management issues, such as food storage and logistics, trade and consumption. This study based on the concepts, principles and methods of plant taxonomy and chemical taxonomy, and it analyzes historical documents, origins and evolution, internal relationships, and management needs; According to the four principles of flour production (pasta) raw materials, production processes, product forms and properties, consumption methods and habits, clarify the interrelationship between them. Chinese flour products are divided into cakes or pie, noodles, steamed breads, starch-based products and fried flour products, etc. The common names were clarified, the classification tree of flour products was preliminarily established, and the problems encountered in the classification process were discussed. In a sense, the classification of flour products is a preliminary exploration or generalization of the relationships between foods, the evolution of diets, and the connections between food supply and human evolution. It can also provide a basis or reference for food industry and food market management.